If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = l * 4 * 3 Reorder the terms for easier multiplication: 60 = 4 * 3l Multiply 4 * 3 60 = 12l Solving 60 = 12l Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-12l' to each side of the equation. 60 + -12l = 12l + -12l Combine like terms: 12l + -12l = 0 60 + -12l = 0 Add '-60' to each side of the equation. 60 + -60 + -12l = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -12l = 0 + -60 -12l = 0 + -60 Combine like terms: 0 + -60 = -60 -12l = -60 Divide each side by '-12'. l = 5 Simplifying l = 5
| 12x^2+25= | | 50x-40(x-2)=90 | | 4x^2-16x+32= | | -2(y-7)-4= | | 13x+5(3-5x)= | | -3(5s-6)-18=-3(9s+2)-3 | | -(3x+4)-(-2x-6)=13 | | a^2=0.5 | | 2(t-6)+6t=4(2t+3)-8 | | 5.3q-4.9-6.7q=-2.7-1.4q-2.2 | | 7(x-4)+7=2x+5(-4+x) | | 8g+1=15g-6 | | log[2](3*10x-22)=3 | | log[2]((3)(10x)-22)=3 | | 2x+p-7x+2p= | | (2x+y)+(3x+y)= | | 20+(-3)=17 | | 28+a=-16 | | 4x-7=17+7x | | 0.007x^2+0.02x=150 | | 3(2x-5)=5x-26 | | 14x=-19 | | 2a-3b+4a-b+6a+4b=180 | | -20p(3p-2)(3p-2)-20(3p-2)p-5p=-45p(2p-1)(2p-1) | | 21x^2+25x-56=0 | | 121h^2=225 | | X^3-14x+24=0 | | -2(4x)-1=4x | | 36000*x=7200*x*x | | 25w^2-144=0 | | X^3-14x^2+24=0 | | 31x+x^4=-1 |